Early Detection and Correction of Cerebral Desaturation With Noninvasive Oxy-Hemoglobin, Deoxy-Hemoglobin, and Total Hemoglobin in Cardiac Surgery: A Case Series. (16th November 2022) - Calderone, Alexander; Jarry, Stéphanie; Couture, Etienne J.; Brassard, Patrice; Beaubien-Souligny, William; Momeni, Mona; Liszkowski, Mark; Lamarche, Yoan; Shaaban-Ali, Mohamed; Matta, Basil; Rochon, Antoine; Lebon, Jean-Sébastien; et al.
Abstract : Regional cerebral oxygen saturation (rSo 2 ) obtained from near-infrared spectroscopy (NIRS) provides valuable information during cardiac surgery. The rSo 2 is calculated from the proportion of oxygenated to total hemoglobin in the cerebral vasculature. Root O3 cerebral oximetry (Masimo) allows for individual identification of changes in total (ΔcHbi), oxygenated (Δo 2 Hbi), and deoxygenated (ΔHHbi) hemoglobin spectral absorptions. Variations in these parameters from baseline help identify the underlying mechanisms of cerebral desaturation. This case series represents the first preliminary description of Δo 2 Hbi, ΔHHbi, and ΔcHbi variations in 10 cardiac surgical settings. Hemoglobin spectral absorption changes can be classified according to 3 distinct variations of cerebral desaturation. Reduced cerebral oxygen content or increased cerebral metabolism without major blood flow changes is reflected by decreased Δo 2 Hbi, unchanged ΔcHbi, and increased ΔHHbi Reduced cerebral arterial blood flow is suggested by decreased Δo 2 Hbi and ΔcHbi, with variable ΔHHbi. Finally, acute cerebral congestion may be suspected with increased ΔHHbi and ΔcHbi with unchanged Δo 2 Hbi. Cerebral desaturation can also result from mixed mechanisms reflected by variable combination of those 3 patterns. Normal cerebral saturation can occur, where reduced cerebral oxygen content such as anemia is balanced by a reduction in cerebral oxygen consumption such as during hypothermia. A summative algorithm using rSo 2, Δo 2 Hbi, ΔHHbi, and ΔcHbi is proposed. Further explorations involving more patients should be performed to establish the potential role and limitations of monitoring hemoglobin spectral absorption signals.